A Rare Cause of Intrauterine Plagiocephaly within Twin Pregnancy: A Case Report - Mustafa Ulubay; Fahri Burçin Fıratlıgil; İbrahim Alanbay; Uğur Keskin; Ulaş Fidan; Ali Ergün (Medical Network, 2016)
The word plagiocephaly is occurred from Greek for "slanted" (plagio) and "head" (kephale). Plagiocephaly describes a planar or multiplanar cranial asymmetry which can be occurred in prenatal or postnatal period. In prenatal period, the most reason for associated plagiocephaly is intrauterine pressure (multiple birth infants (especially dizygotic twins), amount of amniotic, small pelvis and uterine tumors etc.). It has been demonstrated in recent studies that the location of the fetuses within uterus, importantly their position and orientation in the uterus and also the number of fetuses play crucial roles in the development of plagiocephaly during pregnancy. In this report, it was reported that in the case of the dizygotic twin- pregnancy due to the location of the babies in the uterus, they are prone to develop plagiocephaly.